Optimum parity of volumes of training loadings in the one-cyclic experimental period of preparation taekwondo athletes high qualification - Saienko V.G; Michelman S.V (Kharkov National Pedagogical University, 2010)
Efficiency of application of correlation of volumes of the trainings loadings is tested in preparation of sportsmen. 12 sportsmen took part in an experiment (age of 18-22, experience of employments from 8 to 15 years). On the extent of three months the program of preparation was used. All sportsmen conducted the identical amount of trainings employments - 105. The most effective construction of training process of sportsmen is certain in one-cyclic three months period. It has such correlation of volumes of trainings facilities: base technique - 10%, formal complexes of battle exercises - 9%, specially-preparatory exercises - 24%, exercises on shells - 17%, exercises with a partner - 17%, sparrings - 23%.